The Influence of Auditor’s Education Level, Accounting Education, Public Accountant Firm Size on Accounting Profession: Implication to Good Corporate Governance in Indonesia - Tandiontong, Mathius; Sinuraya, Candra; Rajagukguk, Sondang Mariani (Master of Management Study Program, Faculty of Business and Economics - Petra Christian University, 2019)
Principles of good corporate governance work well in every business entity, if the role of the accounting profession functions properly. For the accounting profession can play a good role is determined by the level of adequate auditor education, the quality of accounting education, magnitude and the number of public accounting firms spread evenly throughout the territory of Indonesia. The purpose of this study is to test empirically the influence of auditor education level, accounting education, the amount of public accounting firm to the accounting profession and its implications for the application of the principles of good corporate governance in Indonesia. The research method used in this research is descriptive verification by using quantitative approach. Data were collected through indirect communication techniques using questionnaires, limited interviews, and documentation studies in an effort to add explanatory elements to the survey results. The unit of analysis is the Public Accounting Firm in the island of Java. Sampling with simple random proportional method to 88 respondents received by researchers from 500 respondents sent. The technique of analysis and data testing is done by Path analysis. The results showed that: (1) There is a correlation between the level of accountant education with accounting education and the magnitude of public accounting firms with the level of keeratanya still at a moderate level. (2) Coefficient of Determination of Education Level Auditor, Accounting Education, and Quantity of Public Accounting Firm simultaneously have positive effect on Accounting Profession. However, partially the Auditor's Education Level and the Magnitude of Public Accounting Firm have an influence on the Accounting Profession is not significant. (3) There is influence of education level of Auditor, Accounting Education, Accountant Public Accountant Level and Accounting Profession partially or simultaneously to the application of Good Corporate Governance principles. Partially, however, the level of Education of Auditor and the magnitude of Public Accounting Firm influences the application of Good Corporate Governance principles but not significant.